An evaluation of a model for automated assessment of information system students’ contributions to internet forum / Mee Chin Wee and Zaitun A. B. - Mee, Chin Wee; A. B., Zaitun (Penerbit UiTM (UiTM Press), 2008)
Students collaboration via discussion in an Internet forum when working on a project for Information Systems (IS) courses is common in Malaysia. Assessing students’ contributions to Internet forums has become important. However, manually assessing students’ contributions to Internet forums is a time consuming task. A model was proposed to help IS educators in assessing students’ contributions to an Internet forum. This paper reports on the evaluation of the proposed model incorporated into an Internet forums to generate performance indicator scores for students’ contributions. The evaluation was carried out in Malaysia. The evaluation results show that the assessment model can be used to predict IS students’ marks for their contributions to Internet forums.